CARIBOU‐1: A pilot controlled trial of an Integrated Care Pathway for the treatment of depression in adolescents. Issue 2 (27th May 2022) - Courtney, Darren B.; Cheung, Amy; Henderson, Joanna; Bennett, Kathryn; Wang, Wei; Chen, Sheng; Battaglia, Marco; Strauss, John; Mitchell, Rachel; Wang, Karen; Relihan, Jacqueline; Prebeg, Matthew; et al.
Abstract: Background: To co‐ordinate a multidisciplinary team in the delivery of guideline recommendations using a measurement‐based care framework, our group previously developed a care pathway for the treatment of depression in adolescents. Core components of the pathway were: assessment, education, cognitive‐behavioural therapy, a caregiver intervention group, a medication algorithm, and monthly measurement‐based care "team reviews" with the adolescent present. The aim of this study was to test the feasibility of conducting a controlled clinical trial of the pathway. Method: We conducted a 20‐week pilot controlled clinical trial of the care pathway relative to treatment as usual. Participants were adolescents (age 14–18) with a primary diagnosis of Major Depressive Disorder recruited from one of two outpatient psychiatric clinics at academic hospitals. Site of presentation was the method of allocation. Thirty‐five youth were allocated to the pathway and 31 were allocated to treatment as usual. As this is a pilot study, trial feasibility outcomes were of primary interest, including clinician fidelity to the care pathway. Results: Our target sample size was recruited over a 15‐month time interval. Clinician fidelity and adolescent engagement in the care pathway components on a priori checklists were high (95% and 80%, respectively). We collected baseline and 20‐week endpoint data for our primary outcome of the Children's Depression Rating Scale – Revised (CDRS‐R) for 83% of the sample. On linear mixed effects modelling, we observed a linear decrease in CDRS‐R across 4‐week intervals up to the 20‐week endpoint in both groups ( β = −2.07; 95% CI −3.14 to −1.01). Conclusion: A controlled clinical trial of a complex, multi‐component intervention for the treatment of depression in adolescents is feasible. Given the need to find optimal strategies to deliver effective care for adolescents with depression, a definitive randomized controlled trial of the pathway is warranted. Trial is registered at Clinicaltrials.gov : NCT03428555 Abstract : We conducted a pilot controlled clinical trial for the treatment of depression in adolescents comparing a care pathway relative to treatment‐as‐usual. The trial demonstrated feasibility with respect to recruitment, adherence to the pathway and data collection efficiency.